Pelatihan Pembuatan Bahan Ajar Komik Digital Berbasis Kearifan Lokal Suku Pamona untuk Meningkatkan Literasi Digital di SDN 2 Tonusu Kabupaten Poso [Training on Creating Digital Comic Teaching Materials Based on Local Wisdom Pamona Tribe to Improve Digital Literacy at SDN 2 Tonusu Poso Regency] - Nashrullah, Nashrullah; Hariana, Kadek; Lagandesa, Yun Ratna; Lapasere, Sisriawan; Alfulaila, Noor; Ratu, Bau; Deviyanti, Ida Ayu Putu Puja (UKInstitute, 2026)
To improve digital literacy at Tonusu 2 Public Elementary School in Poso Regency, a community service program was designed with a focus on training in the creation of digital comic teaching materials based on the local wisdom of the Pamona tribe. Local wisdom provides a strong foundation for developing teaching materials because it can connect learning to students' cultural contexts, making it more relevant and engaging. The main objective of this program is to improve digital literacy among teachers and students at Tonusu 2 Public Elementary School while strengthening local cultural identity. The first step was to conduct a series of intensive training sessions for Tonusu 2 Public Elementary School teachers in digital comic creation. This training involved teaching technical skills in using digital comic creation software as well as pedagogical approaches for integrating local wisdom into teaching material content. After the training, teachers were asked to apply the skills they learned by creating digital comics relevant to the daily lives and cultural values of the Pamona tribe. Furthermore, the digital comics created will be used in the learning process at SDN 2 Tonusu. Abstrak. Dalam rangka meningkatkan literasi digital di Sekolah Dasar Negeri (SDN) 2 Tonusu, Kabupaten Poso, sebuah program pengabdian kepada masyarakat dirancang dengan fokus pada pelatihan pembuatan bahan ajar komik digital berbasis kearifan lokal suku Pamona. Kearifan lokal menjadi landasan yang kuat dalam pengembangan bahan ajar karena dapat mengaitkan pembelajaran dengan konteks budaya siswa, sehingga lebih relevan dan menarik minat belajar. Tujuan utama dari program ini adalah untuk meningkatkan literasi digital di kalangan Guru dan Siswa SDN 2 Tonusu sambil memperkuat identitas budaya lokal. Langkah pertama adalah menyelenggarakan serangkaian pelatihan intensif bagi guruguru SDN 2 Tonusu dalam pembuatan komik digital. Pelatihan ini melibatkan pengajaran keterampilan teknis dalam penggunaan perangkat lunak pembuatan komik digital serta pendekatan pedagogis dalam mengintegrasikan kearifan lokal ke dalam konten bahan ajar. Setelah pelatihan, guru-guru diminta untuk menerapkan keterampilan yang mereka pelajari dengan membuat komik digital yang relevan dengan kehidupan sehari-hari dan nilai-nilai budaya suku Pamona. Selanjutnya, komik-komik digital yang telah dibuat akan digunakan dalam proses pembelajaran di SDN 2 Tonusu.